Importance of Image Guidance in Glenohumeral Joint Injections: Comparing Rates of Needle Accuracy Based on Approach and Physician Level of Training. (January 2016) - Mattie, Ryan; Kennedy, David J.
ABSTRACT: Objective: This study compared the accuracy of blind glenohumeral joint (GHJ) injections between physical medicine and rehabilitation interventional fellows (inexperienced provider) and a sports medicine board–certified physical medicine and rehabilitation attending physician (experienced provider) using either an anterior or posterior approach. Methods: A retrospective analysis of 162 consecutive patients comprising 165 GHJ injections was performed. All GHJ injections were initially placed via anatomic landmark guidance by either an experienced or an inexperienced provider. Contrast medium using live fluoroscopy was injected to determine if intra-articular placement had been obtained. Results: The overall accuracy of a blind GHJ injection, regardless of the provider level of experience, was 45.5%. The inexperienced provider was accurate 37.6% of the time, and the experienced provider was accurate 64.6% of the time. The difference in provider accuracy based on level of experience was shown to be statistically significant at P less than 0.05. There was no statistically significant difference between the anterior and posterior approaches regardless of physician level of experience. Conclusions: The results of this study suggest that image guidance is an important utility for accurate navigation into the GHJ space regardless of the level of training. Neither the anterior nor the posterior approach proved to be significantly more accurate.